Deep Neural Control Module (DNCM)AI-Driven Adaptive Deep LearningControl Framework for Islanded DCMicrogrids in Space Habitats and UAVs (International Journal of Scientific Research and Management (IJSRM), 2025)
Islanded DC microgrids are pivotal for ensuring autonomous, resilient, and efficient power systems in space habitats and unmanned aerial vehicles (UAVs). Recent research and development by NASA, Boeing, and the U.S. Air Force have focused on integrating solar photovoltaic (PV) systems with advanced energy storage solutions to support off-grid operations. This paper presents a comprehensive and uniquely conceptualized model that combines deep learning, artificial intelligence algorithms, and advanced optimization techniques for the control, stability, error detection, and power optimization of Islanded DC Microgrids used in space habitats and UAVs.